PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION BERBANTUAN MEDIA CANVA TERHADAP PENINGKATAN HASIL BELAJAR IPAS - Nuri Nur Akmar; Jaka Permana; Sopyan Hendrayana (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of the cooperative learning model Student Teams Achievement Division (STAD) assisted by Canva media on students' learning outcomes in the Natural and Social Sciences (IPAS) subject, specifically on the topic